A Cyclic (Alkyl)(boryl)germylene Derived from a Cyclic (Alkyl)(amino)germylene. Issue 50 (23rd October 2019) - Rao, Bin; Kinjo, Rei
Abstract: A cyclic (alkyl)(amino)germylene undergoes a ring expansion reaction with dibromomesitylborane (MesBBr2 ) to afford a six‐membered dibromogermane derivative. In the presence of Lewis bases (PMe3 or Me NHC), reduction of the latter with two equivalents of potassium graphite (KC8 ) gives rise to cyclic (alkyl)(boryl)germylene–Lewis base adducts. Upon heating, the germylene—PMe3 adduct reacts with H2 to yield a germane, probably via a base‐free germylene featuring a small HOMO–LUMO gap. Abstract : Ring expansion of a five‐membered cyclic (alkyl)(amino)germylene with a dihaloborane followed by reduction in the presence of Lewis base affords six‐membered cyclic (alkyl)(boryl)germylene–Lewis base adducts. Upon heating, the latter not only undergo dimeric skeletal isomerization to give a cyclic (alkyl)(germyl)germylene featuring η 3 ‐coordination, but also react with H2 .